Some aspects of the use of herbs in the treatment of conjunctivitis - Matysik-Woźniak, Anna; Matysik, Elżbieta; Weryszko-Chmielwska, Elżbieta; Paduch, Roman (Polish Journal of Public Health, 2011)
Herbal preparations are presently enjoying a higher degree of confidence among patients both in the developed and developing world. For ages such preparations have been employed in the treatment of conjunctivitis and inflammation of eyelids due to the antibacterial, antiviral and antifungal properties of their various components.Infusions prepared from some plants are believed to act as antiallergens, anticongestants, antiinflammators; hence the treatment of ocular disease conditions may turn out to be more complex. The spreading condition of antibiotic resistance of bacteria makes it necessary to search for new antimicrobic substances. It seems that some herbs may act as supplementary in antibiotic therapy in ophthalmology, and in some cases they may curtail the use of antibiotics. The choice of the herbal preparation is of vital importance, as well as its standardization based on scientific research on, among other methods, cell lines and animals. This allows for elimination of components that have toxic or allergenic properties. The present paper deals in detail with plantain (Plantago lanceolata L.) and eyebright (Euphrasia officinalis L.) considering their application in ophthalmology.